1994
DOI: 10.1007/bf02600026
|View full text |Cite
|
Sign up to set email alerts
|

A computerized intervention to improve timing of outpatient follow-up

Abstract: Recommendations based on nonlinear optimization prompted clinicians to schedule less frequent follow-up for patients taking warfarin, with no deterioration in anticoagulation control. This approach to scheduling can potentially reduce utilization while maintaining quality of care for patients who require long-term monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Most were used by physicians for decision making, (28/33, 85%) [4-19,21,23,24,26-37], the rest by other health professionals. Recommendations were usually delivered at the time of care (27/31, 87%) [4-7,10-14,16-19,21-26,29-32,34-39] on a desktop or laptop computer (16/25, 64%) [4,10,15,16,18,21,23-26,30-34,39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most were used by physicians for decision making, (28/33, 85%) [4-19,21,23,24,26-37], the rest by other health professionals. Recommendations were usually delivered at the time of care (27/31, 87%) [4-7,10-14,16-19,21-26,29-32,34-39] on a desktop or laptop computer (16/25, 64%) [4,10,15,16,18,21,23-26,30-34,39].…”
Section: Resultsmentioning
confidence: 99%
“…Most were used by physicians for decision making, (28/33, 85%) [4-19,21,23,24,26-37], the rest by other health professionals. Recommendations were usually delivered at the time of care (27/31, 87%) [4-7,10-14,16-19,21-26,29-32,34-39] on a desktop or laptop computer (16/25, 64%) [4,10,15,16,18,21,23-26,30-34,39]. Pilot testing was done in 48% (13/27) [6,8,9,16,20,22,24-26,30,33,34,39], training was provided to users in 55% (17/31) [6,7,9,10,12,17,19,20,24,25,27,28,30,31,33-37,39], and the authors were the developers of the CCDSS in 59% (17/29) of studies [5-7,10,11,13,16,19,21,22,26,30-34,39].…”
Section: Resultsmentioning
confidence: 99%
“…(6-10) However, few studies assess how CDS content influences physician use. (11) One study provides a framework for assessing CDS content in terms of clinical appropriateness, defined as correct and current for the patient, according to expert review of the alerts.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that a longer anticoagulation may be helpful [3], particularly in cases where venous thrombosis was not associated with a reversible risk factor [4]. Bleeding is by far the most important complication of the oral anticoagulation [5][6][7][8][9]. Much effort has been devoted to improve the safety of oral anticoagulation by adopting a series of measures (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, the bleeding risk remains significantly high [10]. Many studies have been carried out to identify high-risk patients [5][6][7][8][9][10]. The overall incidence of bleeding episodes was lower among individuals aged 70 years or less and in patients with lower intensity regimens of oral anticoagulation [9].…”
Section: Introductionmentioning
confidence: 99%